Physiological and Behavioural Response of Broilers Fed Wet Mash with or Without Drinking Water During Wet Season in the Tropics - Awojobi, H.A.; Buraimo, R.O.; Oluwole, B.O. (International Journal of Poultry Science, 2011)
The effect of wet feeding with or without drinking water on rectal temperature, respiratory rate, behavioural pattern (panting, eating and resting), haematological and serum biochemistry of broilers was investigated. Seventy (70), six weeks old broilers were used for the study. The treatments consist of: Conventional dry mash and Wet mash with varying amounts of water addition (1.0, 1.5, 2.0 parts of water to 1 part of feed) with or without drinking water. Mixing was done at the time of feeding. Results showed that there was no significant relationship between behavioural pattern (panting, eating and resting) and feeding form in the morning (p>0.05, X2 = 0.52), afternoon (p>0.05, X2 = 3.28) and evening (p>0.05, X2 = 0.94). Respiratory rate was significantly (p<0.05) affected by feeding form. The adaptive mechanisms of panting and increased rate of respiration ensured that rectal temperature was not significantly (p>0.05) affected by feeding form. Heamatological indices did not show any significant (p>0.05) variation with the application of wet feed with or without drinking water. However, WBC differentials for oesinophils and monocytes were significantly (p<0.05) affected. Serum urea levels and electrolytes (Na+, Ca+, K+, HCO3- and Cl-) were significantly (p<0.05) affected by the use of wet feeding. Serum electrolyte results suggest a slight disturbance in the maintenance of water/electrolytes balance in all wet feed birds except W+1.0.